2009
DOI: 10.1200/jco.2008.17.5984
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Trial of Erlotinib Versus Temozolomide or Carmustine in Recurrent Glioblastoma: EORTC Brain Tumor Group Study 26034

Abstract: Erlotinib has insufficient single-agent activity in unselected GBM. No clear biomarker associated with improved outcome to erlotinib was identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
250
1
7

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 486 publications
(271 citation statements)
references
References 19 publications
7
250
1
7
Order By: Relevance
“…This would be in agreement with the other authors that have postulated that tumors harboring certain point mutations, as well as the vIII deletion, would be more responsive to dacomitinib (21). In fact, the presence of EGFRvIII, in a wild-type PTEN context, had been associated with GBM response to erlotinib (15), although this could not be confirmed in subsequent trials (24). Retrospective analysis of the two current phase II clinical trials would help to solve these discrepancies.…”
Section: Discussionsupporting
confidence: 59%
“…This would be in agreement with the other authors that have postulated that tumors harboring certain point mutations, as well as the vIII deletion, would be more responsive to dacomitinib (21). In fact, the presence of EGFRvIII, in a wild-type PTEN context, had been associated with GBM response to erlotinib (15), although this could not be confirmed in subsequent trials (24). Retrospective analysis of the two current phase II clinical trials would help to solve these discrepancies.…”
Section: Discussionsupporting
confidence: 59%
“…Nitrosoureas [52][53][54][55][56] and 1 trial with carmustine where data for patients treated with carmustine (n=29) were not separately reported but summarized in a common "control" arm with 27 patients receiving TMZ [57]. All but 3 trials were conducted at the first recurrence after TMZ-based standard radiochemotherapy.…”
Section: Nitrosourea Monotherapy and Combination Regimensmentioning
confidence: 99%
“…All but 3 trials were conducted at the first recurrence after TMZ-based standard radiochemotherapy. One study was done in chemotherapy-naïve-patients [47], one study did not disclose previous chemotherapy except exclusion of nitrosourea, bevacizumab or investigational agents [53], one study reported previous chemotherapy in about 60% of the patients without details [57]. PFS-6 ranged between 17.5% and 61.5% and median OS between 6.0 and 11.1 months for monotherapy of nitrosourea agents.…”
Section: Nitrosourea Monotherapy and Combination Regimensmentioning
confidence: 99%
See 1 more Smart Citation
“…A subset of glioblastomas exhibit overexpression of egfr and EGFR gene amplification 111 , and several trials have investigated the egfr tyrosine kinase inhibitors erlotinib, gefitinib, and lapatinib. However, a phase ii trial that compared erlotinib with active controls (temozolomide or carmustine) reported a 6-month pfs of only 11.4% as compared with 24% for controls 112 . Other trials have reported little or no benefit for erlotinib used as a single agent or in combination with carboplatin or sirolimus, a mammalian target of rapamycin (mtor) inhibitor [113][114][115] .…”
Section: 64mentioning
confidence: 99%